Multiport Routing of Topologically Optical Transport Based on Merging of Valley-Dependent Edge States and Second-Order Corner States - Li, Meng-Yu; Chen, Wen-Jie; He, Xin-Tao; Dong, Jian-Wen (Frontiers in Physics, 2022)
Topological photonics provide a novel platform to robustly manipulate the flow of light and design high-performance nanophotonic devices. To do this, a fundamental mechanism is the flexible control of optical transport based on topological boundary states on edges or corners. In this work, we design a multiport device to route the topologically optical transport by using both valley-dependent edge states (VDESs) and second-order corner states (SOCSs). The VDESs are derived from sublattice symmetry breaking in a honeycomb lattice, while SOCSs are induced by the lattice deformation of Kagome lattice. In terms of unit cell, we find that both configurations can be reconsidered as the same triangular-lattice photonic crystal, which consists of a hexagon-profile air hole array in silicon background. Therefore, a four-port device is designed based on the two configurations. In simulation, we observe the frequency-dependent routing effect of the topologically optical transport by merging of VDESs and SOCSs. This work not only shows a novel platform to explore various topological phases in the photonic system but also provides guidance in the development of topological photonic integrated circuits with mode division multiplexing.